Escape from Human Immunodeficiency Virus Type 1 (HIV-1) Entry Inhibitors - Carol D. Weiss; Christopher J. De Feo (Viruses, 2012)
The human immunodeficiency virus (HIV) enters cells through a series of molecular interactions between the HIV envelope protein and cellular receptors, thus providing many opportunities to block infection. Entry inhibitors are currently being used in the clinic, and many more are under development. Unfortunately, as is the case for other classes of antiretroviral drugs that target later steps in the viral life cycle, HIV can become resistant to entry inhibitors. In contrast to inhibitors that block viral enzymes in intracellular compartments, entry inhibitors interfere with the function of the highly variable envelope glycoprotein as it continuously adapts to changing immune pressure and available target cells in the extracellular environment. Consequently, pathways and mechanisms of resistance for entry inhibitors are varied and often involve mutations across the envelope gene. This review provides a broad overview of entry inhibitor resistance mechanisms that inform our understanding of HIV entry and the design of new inhibitors and vaccines.